ANALISIS PEMIKIRAN PENDIDIKAN ISLAM IBNU KHALDUN DALAM REKONSTRUKSI PENDIDIKAN INDONESIA - Muhammad Nurul Khakim; Moh Sugeng (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The decline of Islamic education can be seen from different sectors, concepts, systems, curriculum, methods that are considered less relevant to society’s needs. Whereas in reality our society, we are experiencing a period of transition and the impact of modernity may undermine purity and wholeness of the existence of Islamic education. The author tries to offer some ideas by the thinking offered by Islamic education experts, one of them was Ibn Khaldun, who was born in Tunisia in Ramadan 732/1332 c.e. The purpose of this study is to explain several concepts of Islamic education according to Ibn Khaldun, explain the national education system and explain the relevance between the concept of Islamic education according to Ibn Khaldun and the National Education System. The method used is literature study with a historical approach. The conclusion in this study is to explain that the education and teaching of Ibn Khaldun, is not only concerned with religion, but also from a worldly perspective, both of which must be equally given to students. The Ibn Khaldun paradigm of education in essentially more important and focused the concept of education to the formation of behavior, morals and civility. Ibn Khaldun's thoughts have relevance to Islamic education in Indonesia today. The role of Islamic education in the National Education System must be emphasized by coloring to the scientific practice carried out. Islamic education is not just teaching religious studies, but all knowledge actually comes from Allah SWT.